Physical-menstrual variables as predictors of women's rugby performance and well-being - Liébana, E.; Muñoz-Aloy, A.; Gutiérrez, S.; García-Guillot, S.; Sanchís, C.; Monleón, C. (European Journal of Human Movement, 2025)
Women`s rugby is characterized by an intermittent activity profile that includes high-intensity actions such as sprinting, tackling, scrummaging, and rucking. Therefore, investing training time in the development of strength, power, and overall well-being may contribute to enhanced performance. This study analyzed the effects of different phases of the menstrual cycle on the performance and perceived well-being of female amateur rugby players. The sample consisted of 16 female players (22.13 ± 4.50 years). The variables analyzed included body composition, stretch-shortening cycle (CMJ, CMJ Abalakov, and CMJ unilateral), isometric strength, and state of well-being. Menstrual cycle phases were monitored using the "My FLO menstrual calendar" application. The results showed no significant differences in the stretch-shortening cycle or isometric strength test results across the menstrual cycle phases (p > .05). However, total body weight had a significant effect on right/left leg strength (p = .020). Regarding perceived well-being, a significant variation was observed during the ovulatory phase (p = .0226), with fat mass identified as an influential factor (p = .172). A difference in CMJ was also observed between the menstrual and ovulatory phases (p = .019). The results suggest that, although strength is not altered by the menstrual cycle, variables such as total body weight and fat mass influence both strength and well-being in female rugby players across the menstrual cycle. These results highlight the importance of individualizing training loads according to body composition profiles and well-being status throughout the menstrual cycle.